Pandemic, audiovisual on social networks and reactive forces that depotentialize thinking about spatiality - pimenta, thiago albano (Geografares, 2021)
This work seeks to analyze two audiovisuals (assemblies between video, audio and speeches that are coming) that are related to the pandemic context. These occupy social networks, one on YouTube, the other on Facebook. We want to focus on the understanding of the speeches and narratives that they circulate, as well as the forces that compose them and how they intermingle in a mode of subjectification of this Covid-19 pandemic. Given the above, we want to provoke readers to pay attention to these assemblages in order to understand them better, as well as to create and enable other forms of assemblage that eradicate these forces, opening space to think otherwise.
Keywords: Pandemic; Audio-visual; Geographic space